2012
DOI: 10.1128/jvi.00750-12
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Induces Epidermal Growth Factor Receptor Activation via CD81 Binding for Viral Internalization and Entry

Abstract: While epidermal growth factor receptor (EGFR) has been shown to be important in the entry process for multiple viruses, including hepatitis C virus (HCV), the molecular mechanisms by which EGFR facilitates HCV entry are not well understood. Using the infectious cell culture HCV model (HCVcc), we demonstrate that the binding of HCVcc particles to human hepatocyte cells induces EGFR activation that is dependent on interactions between HCV and CD81 but not claudin 1. EGFR activation can also be induced by antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(150 citation statements)
references
References 57 publications
7
142
1
Order By: Relevance
“…Antibodies to CD81, TfR1, or isotype control IgG were added to parallel cultures before virus binding or after virus binding at hour intervals after the temperature shift. Exactly as previous groups have observed (31,32), when normalized to the IgG control at each time, anti-CD81 lost its inhibitory effect by 2 h postbinding. In contrast, addition of anti-TfR1 inhibited HCV by more than 50% until 4 h after the temperature shift, indicating that TfR1 functions in HCV entry at a step after CD81 (Fig.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Antibodies to CD81, TfR1, or isotype control IgG were added to parallel cultures before virus binding or after virus binding at hour intervals after the temperature shift. Exactly as previous groups have observed (31,32), when normalized to the IgG control at each time, anti-CD81 lost its inhibitory effect by 2 h postbinding. In contrast, addition of anti-TfR1 inhibited HCV by more than 50% until 4 h after the temperature shift, indicating that TfR1 functions in HCV entry at a step after CD81 (Fig.…”
Section: Resultsmentioning
confidence: 77%
“…To determine when TfR1 acts during entry relative to other HCV entry factors, we used a previously published antibody time-of-addition strategy (23,31,32). The strategy is based on the principle that blocking antibodies lose their inhibitory activity when applied after the targeted protein has already served its function.…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Diao and colleagues demonstrated that direct hepatitis C virus (HCV) binding to CD81 can induce EGFR activation and internalization [62]. HCV interaction with CD81 can also activate multiple downstream signaling pathways including Rho GTPase family members, Cdc42, MAPK pathways, and members of the ezrin-radixin-moesin (ERM) family of proteins [63][64][65].…”
Section: Macropinocytosismentioning
confidence: 99%
“…Specifically, CD81 forms a coreceptor complex with the tight junction protein claudin-1 (CLDN1) [49,50] and is engaged in late events of HCV entry [51]. This re-localization and virusreceptor complex association with CLDN1 involves multiple signaling pathways (e.g., Rho GTPases, PI3K/AKT, and ERK/MAPK) [52,53], includes the activation of host cell kinases such as the epidermal growth factor receptor (EGFR) and ephrin receptor A2 (EphA2) [54,55], and is influenced by the absence of the CD81-associated partner EWI-2wint on the hepatocytes [56,57]. The EWI-2wint molecule is normally bound to CD81 on most cell type surfaces and inhibits its diffusion which is required to promote HCV entry; however, it is not expressed in the hepatocytes, and hence its absence has been suggested to contribute to the restricted tropism of the virus [56].…”
Section: Overview Of Hcv Entrymentioning
confidence: 99%